Predictive and Prognostic Value of DNA Damage Response Associated Kinases in Solid Tumors - Gachechiladze, Mariam; Skarda, Josef; Bouchalova, Katerina; Soltermann, Alex; Joerger, Markus (Frontiers in Oncology, 2020)
Dysfunctional DNA repair with subsequent genome instability and high mutational burden represents a major hallmark of cancer. In established malignant tumors, increased DNA repair capacity mediates resistance to DNA-damaging therapeutics, including cytotoxic drugs, radiotherapy, and selected small molecules including inhibitors of poly (ADP-ribose) polymerase (PARP), Ataxia Telangiectasia Mutated (ATM), ataxia telangiectasia and Rad3-related protein (ATR), and Wee1 kinase (Wee1). In addition, DNA repair deficiency is not only associated with sensitivity to selected anticancer drugs, but also with increased mutagenicity and increased neoantigen load on tumor cells, resulting in increased immunogenicity and improved response to CTLA4- or PD-(L)1 targeting monoclonal antibodies. DNA damage response (DDR) is composed of complex signalling pathways, including the sensing of the DNA damage, signal transduction, cellular response pathways to DNA damage, and activation of DNA repair. DNA double strand breaks (DSBs) are the most dangerous form of DNA damage. Tumor cells are characterised by frequent accumulation of DSBs caused by either endogenous replication stress or the impact of cancer treatment, most prominently chemotherapy and radiotherapy. Therefore, response of cancer cells to DSBs represents a crucial mechanism for how tumors respond to systemic treatment or radiotherapy, and how resistance develops. Ample clinical evidence supports the importance of DDR associated kinases as predictive and prognostic biomarkers in cancer patients. The ATM-CHK2 and ATR-CHK1-WEE1 pathways initiate DNA DSB repair. In the current review, we focus on major DDR associated kinases including ATM, ATR, CHK1, CHK2, and WEE1, and discuss their potential prognostic and predictive value in solid malignancies.